Systematic review of gut microbiota composition, metabolic alterations, and the effects of treatments on PCOS and gut microbiota across human and animal studies - Hanna, Aya; Abbas, Hassan; Yassine, Fayez; AlBush, Alia; Bilen, Melhem (Frontiers in Microbiology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is an endocrine disorder affecting around 12% of women globally, associated with infertility and various comorbidities. Emerging evidence suggests a crucial role of gut microbiota in PCOS pathophysiology, prompting research to investigate alterations in gut microbial composition in patients with PCOS.MethodsThis systematic review aims to analyze human and animal studies that compare gut microbiota composition, gut-derived metabolites, and treatment interventions in PCOS patients versus healthy controls. A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science, yielding studies examining gut microbiota, metabolomic shifts, and treatment responses in PCOS models and human populations.ResultsOur analysis revealed decreases in alpha diversity in PCOS patients, with more pronounced changes in beta diversity in animal models. Specific bacterial taxa, such as Bacteroides vulgatus, Escherichia-Shigella and Lactobacillus, showed implication in PCOS pathogenesis, suggesting potential microbial markers. Furthermore, discrepancies between human and animal studies show the need for humanized mouse models to bridge this gap. Interventions like probiotics and fecal microbiota transplantation (FMT) showed varying levels of efficacy, with FMT emerging as a more promising but invasive option, offering live bacteriotherapy as a potential therapeutic alternative. Alterations in gut-derived metabolites, including short-chain fatty acids and bile acids, highlighted the multifaceted nature of PCOS, with implications extending to metabolic, hormonal, and gut-brain axis disruptions.DiscussionIn conclusion, PCOS exhibits complex interactions between gut microbiota and metabolic pathways, necessitating further research with standardized methods and larger sample sizes to elucidate the microbiome's role in PCOS.